2015
DOI: 10.1373/clinchem.2015.238543
|View full text |Cite
|
Sign up to set email alerts
|

Variant Profiling of Candidate Genes in Pancreatic Ductal Adenocarcinoma

Abstract: BACKGROUND: Pancreatic ductal adenocarcinoma (PDAC) has a poor prognosis. Variant profiling is crucial for developing personalized treatment and elucidating the etiology of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Droplet digital PCR (ddPCR) is a next generation digital PCR with greater analytical sensitivity compared to conventional real-time PCR due to an enhanced ability to read nucleic acid at a single molecule level [20]. Viral RNA was extracted from thawed CBM cell pellets (Roche, Basel, Switzerland) and a minimum of 200ug used as template for cDNA synthesis using random primers and M-MLV reverse transcriptase (Promega, Southampton, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Droplet digital PCR (ddPCR) is a next generation digital PCR with greater analytical sensitivity compared to conventional real-time PCR due to an enhanced ability to read nucleic acid at a single molecule level [20]. Viral RNA was extracted from thawed CBM cell pellets (Roche, Basel, Switzerland) and a minimum of 200ug used as template for cDNA synthesis using random primers and M-MLV reverse transcriptase (Promega, Southampton, UK).…”
Section: Methodsmentioning
confidence: 99%
“…After amplification the plate was transferred to the droplet reader to measure the number of positive and negative droplets based on fluorescence amplitude. The number of template molecules per microliter of starting material was estimated by QuantaSoft™ ddPCR software (Bio-Rad, Hercules, US) using an internal Poisson algorithm described previously [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Specific mutations in GNAS and KRAS could predict the progression of intraductal-papillary-mucinous-neoplasmic lesions to pancreas cancer [170], and mutations in KRAS have prognostic value in pancreatic ductal adenocarcinoma [168]. Genomic mutations analysed in 104 triple negative breast cancer cases highlighted the occurrence of frequent alterations in the PI3K pathway and such mutation pattern related to the clinical outcome of patients [151].…”
Section: Cancer Somatic Mutation Analysismentioning
confidence: 99%
“…Mutations in KRAS are present in more than 90% of patients ( 14 ) and are known to be related to the initiation of PDAC ( 15 ). Inactivating mutations of TP53 , CDKN2A , and SMAD4 occurred in 15–80% of PDAC patients and 30–75% had mutations in at least two of the four genes ( 16 18 ). Several studies ( 19 21 ) explored the relationship between driver genes and prognosis and largely found that these genes were associated with disease prognosis.…”
Section: Introductionmentioning
confidence: 99%